THE EFFECTIVENESS OF THE QUANTUM LEARNING LEARNING MODEL BY PAYING ATTENTION TO LEARNING INTEREST IN STUDENT LEARNING OUTCOMES - Syarifah Soraya (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
This study generally aims to determine the effectiveness of Quantum Learning on student learning outcomes. In particular, this study aims to determine the difference in student learning outcomes between those taught with Quantum Learning and lecture methods, to determine the interaction of Quantum Learning and learning interest in student learning outcomes, and to determine the differences in student learning outcomes in high learning interest and low learning interest taught with Quantum Learning and those taught with the lecture method. This research uses an experimental method with factorial experiment design. The hypothesis testing process in this study uses the two-way Anava statistical technique (Two Way Anova). Based on the results of the hypothesis test, it shows that, there are differences in learning outcomes in students taught using Quantum Learning accompanied by high interest in learning of 82.73 with those taught using the lecture method amounting to 48.80. Thus, the results of the study stated that there is an effectiveness of the application of Quantum Learning learning to the learning outcomes of Islamic Cultural History (SKI) and there is an interaction between Quantum Learning and learning interest in SKI learning outcomes, there is also a reduction in learning outcomes in students who have high interest in learning and who have low interest in learning. This implies that in applying the learning model to learning activities, teachers need to pay attention to the level of interest in learning students.